Size and post-tensioning cable force optimization of cable-stayed footbridge. (October 2021) - Atmaca, Barbaros
Abstract: In recent years, the rapidly increasing population of people and vehicles trigger the need for footbridges, especially in city centers. Cable-stayed footbridges (CSFB) are one of the most remarkable options among the other types of footbridges because of many advantages like as pleasing appearance, economic and easy construction so the design of them getting very more important nowadays. This work aims to determine the optimum size and post-tensioning force (PTF) of stay-cables of CSFB via by optimization process integrated metaheuristic algorithm named Jaya, MATLAB codes and Open Applicable Programming Interface (OAPI) properties of SAP2000. The main objective function of the developed optimization process is to minimize the total weight of stay-cables and find the proper PTF applied to the stay-cables at the same time. To illustrate the possibilities of this developed optimization process, double pylon, and modified fan type cable configuration steel CSFB is selected as a numerical example. Object-based structural software, SAP2000, is selected to perform static and dynamic analysis of selected CSFB under the different combinations of self-weight of structural and non-structural elements, live load of pedestrian, wind load, PTF of stay-cable and earthquake loads. At the end of the optimization process, the total weight of the stay-cables of selected CSFB is reduced more than 66% according to existing CSFB. The structural performances of non-optimized and optimized CSFB are given in detail and compared with each other.